Participar para quê?: a participação linguisticamente eficaz e a interação em contextos de ensino-aprendizagem de língua estrangeira: um projeto de intervenção em escolas públicas no Brasil - Fábio Ricardo Peracini (2021)
This dissertation was developed within the scope of the Master in Educational Sciences, in the Childhood, Family and Society domain, at the FPCE of the University of Porto and, in light of the theoretical contributions of Educational Sciences, Childhood Sociology and Applied Linguistics, it intends to understand those relations in the school context, particularly in the case of English language teaching-learning processes in elementary school and by testing a hypothetical teaching material prepared from the interests of pupils through a mixture of different approaches and procedures and emphasizing the participation of children as post-methodological pedagogical strategy. At issue is the research process that supports the elaboration of a dissertation that intends to gather data about the interests of pupils for a future intervention project to be carried out within Brazilian public schools, aiming to promote English language classes with the objective of taking pupils at level B2 of the classification of the Common European Framework for Languages, and then to its presentation. The investigation contextualizes the current situation of language teaching in macro and micro scenarios; the contradiction of children's participation in the daily use of pre-existing teaching materials and the current conditions of teacher training to recognize and effectively use this participation in the classroom. The differential of this type of proposal is also due to its empowering character for all actors, since the procedures would be established by the pupils according to their interests, and the teachers would be, through a process of continuing education, imbued with post-methodological tools to supplement their second language classes according to critical classroom observation. Data collection occurs through a survey applied to students in the 6th and 7th years of municipal public schools in the city of Guarujá, Brazil, and also through semi-directive interviews applied to teachers from the same schools, as well as through official document analysis in Brazil.